A integração do GeoGebra no estudo de funções - Mathias, Daniele Galvão (2019)
Submitted by Aline Batista (alinehb.ufpel@gmail.com) on 2019-07-12T22:36:38Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) d_2016___Daniele.pdf: 10505117 bytes, checksum: 0dafc2eea7ce8d4e3281ab685eae9be8 (MD5)